Trauma freed of the concept of determinism: is it possible to have a dialogue between psychoanalysis and neuroscience around the question of singularity? - Jessica Tran The; Jessica Tran The; Emeric Saguin; Emeric Saguin; François Ansermet; François Ansermet (Frontiers in Psychology)
This article introduces a model of dialogue between psychoanalysis and neuroscience that is based on an account of the economic dimension of trauma. From the outset Freudian theory took into account the singularity of each subject’s response to traumatic events, setting aside any linear paradigm in the causality of symptoms. In 1980, the introduction of the nosographic category of PTSD (post-traumatic stress disorder) within the DSM (Diagnostic and Statistical Manual) contributed to an increased social recognition for sufferers. Yet, it also resulted in a form of standardization in a clinical picture that hitherto had been heterogenous. The result was a deterministic and linear epistemological paradigm whose effects could be normative. Once we have defined the opposition between these two paradigms, we propose demonstrating that a dialogue is possible between psychoanalysis and neuroscience around the concept of ‘trauma’. To do this we will introduce an interdisciplinary approach that is free of the pitfall of determinism, and that seeks to promote the consideration of singularity in clinic practice. From that perspective, the post-traumatic symptom is no longer viewed as the consequence of a particular event, rather it is a construct produced by the subject in their effort to manage what overwhelms them.